1997
DOI: 10.1523/jneurosci.17-21-08451.1997
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Levels of Norepinephrine Transporters in the Locus Coeruleus in Major Depression

Abstract: The norepinephrine transporter (NET) is a membrane protein responsible for termination of the action of synaptic norepinephrine and is a site of action of many drugs used to treat major depression. The present study determined whether the binding of [ 3 H]nisoxetine to the NET is altered in the locus coeruleus (LC) in major depression, using brain tissue collected postmortem from subjects diagnosed with major depression and from age-matched normal control subjects. Thirteen of the 15 major depressive subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
236
2
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(252 citation statements)
references
References 50 publications
9
236
2
5
Order By: Relevance
“…Previous observations reveal that depression is associated with altered concentrations of several noradrenergic proteins in the LC. For example, elevated levels of tyrosine hydroxylase (TH) (Ordway et al, 1994a;Zhu et al, 1999), increased agonist binding to a 2 -adrenergic receptors (Ordway et al, 1994b(Ordway et al, , 2003, and reduced levels of norepinephrine transporters (Klimek et al, 1997) were previously reported in the LC from major depression and in suicide victims. Interestingly, depletion of norepinephrine or repeated stress in rats can increase TH expression, increase binding to a 2 -adrenergic receptors, and/or decrease binding to the norepinephrine transporter (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous observations reveal that depression is associated with altered concentrations of several noradrenergic proteins in the LC. For example, elevated levels of tyrosine hydroxylase (TH) (Ordway et al, 1994a;Zhu et al, 1999), increased agonist binding to a 2 -adrenergic receptors (Ordway et al, 1994b(Ordway et al, , 2003, and reduced levels of norepinephrine transporters (Klimek et al, 1997) were previously reported in the LC from major depression and in suicide victims. Interestingly, depletion of norepinephrine or repeated stress in rats can increase TH expression, increase binding to a 2 -adrenergic receptors, and/or decrease binding to the norepinephrine transporter (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…Abnormalities that have been observed in the LC from human depressives (Klimek et al, 1997;Ordway et al, 1994aOrdway et al, , 1994bOrdway et al, , 2003Zhu et al, 1999) can be reproduced, in part, by chronic stress or pharmacological depletion of norepinephrine in rats (Cubells et al, 1995;Lee et al, 1983;Melia et al, 1992;Torda et al, 1985;U'Prichard et al, 1979;Wang et al, 1998;Zafar et al, 1997). Given that stress activates the LC in laboratory animals (Pavcovich et al, 1990), that chronic stress depletes norepinephrine in the LC (Weiss and Simson, 1986), and that stress is a common precipitator of depression in humans, it seems possible that depression may be associated with elevated excitatory input to the LC.…”
Section: Role Of Glutamatergic Signaling In Depressionmentioning
confidence: 99%
“…A reduction in the level of NE in the synapse appears to down regulate the level of NET [3]. Recent research has clearly demonstrated a close association between the changes in the distribution of NET in the human brain and various diseases including CNS disorders like depression [4] attention deficit hyperactivity disorder (ADHD) [5,6] and Alzheimer's disease [7]. Non-invasive imaging with highly selective radiolabeled probes would allow us to monitor and quantify the effect of treatment (drug occupancy) or the lack thereof on NET.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently, a positive association between a T182C polymorphism in the NET gene and susceptibility to major depressive disorder has been reported in a Japanese population (Inoue et al, 2004). Using brain tissues collected post mortem from patients diagnosed with major depression, Klimek et al (1997) have shown reduced expression of the NET (decreased [ 3 H]nisoxetine binding) in the locus coeruleus as compared to age-matched normal control subjects. These data as well as differential region-specific effects on the NET of repeated administration of ADs (Herbert et al, 2001) have been interpreted as reflecting a compensatory downregulation of the NET in response to an insufficient availability of its substrate NE at the synapse.…”
Section: Introductionmentioning
confidence: 99%